An analysis of the writing skill difficulties of the English Composition I students at the Foreign Language Department of the University of El Salvador - Aragón Jiménez, Claudia Esmeralda
Many students have learned in high school to camouflage their lack of reading and writing skills, so it is often difficult for teachers to identify their weaknesses until students hand in papers or take exams. Then writing deficiencies are obvious. For this reason, it is important to say that academic writing involves many requirements that students must put into practice to avoid difficulties and complications at the moment of writing essays or report papers. Besides, not only self-strategies influence students’ performance, but also the effectiveness of the methods and techniques that teachers apply in their English Composition courses. Each method is useful with some students but fails with others, so writing needs to persist and teachers must take into account other strategies if they want their students to develop effective writing skills. Therefore, students and teachers must work together as a team. If students want to improve their writing skills, only in this way they will have good results and they will notice the difference in their compositions.